Cloning and Characterization of a Flavonol Synthase Gene From Litchi chinensis and Its Variation Among Litchi Cultivars With Different Fruit Maturation Periods - Liu, Wei; Xiao, Zhidan; Fan, Chao; Jiang, Nonghui; Meng, Xiangchun; Xiang, Xu (Frontiers in Plant Science, 2018)
Litchi (Litchi chinensis) is an important subtropical fruit tree with high commercial value. However, the short and centralized fruit maturation period of litchi cultivars represents a bottleneck for litchi production. Therefore, the development of novel cultivars with extremely early fruit maturation period is critical. Previously, we showed that the genotypes of extremely early-maturing (EEM), early-maturing (EM), and middle-to-late-maturing (MLM) cultivars at a specific locus SNP51 (substitution type C/T) were consistent with their respective genetic background at the whole-genome level; a homozygous C/C genotype at SNP51 systematically differentiated EEM cultivars from others. The litchi gene on which SNP51 was located was annotated as flavonol synthase (FLS), which catalyzes the formation of flavonols. Here, we further elucidate the variation of the FLS gene from L. chinensis (LcFLS) among EEM, EM, and MLM cultivars. EEM cultivars with a homozygous C/C genotype at SNP51 all contained the same 2,199-bp sequence of the LcFLS gene. For MLM cultivars with a homozygous T/T genotype at SNP51, the sequence lengths of the LcFLS gene were 2,202–2,222 bp. EM cultivars with heterozygous C/T genotypes at SNP51 contained two different alleles of the LcFLS gene: a 2,199-bp sequence identical to that in EEM cultivars and a 2,205-bp sequence identical to that in MLM cultivar ‘Heiye.’ Moreover, the coding regions of LcFLS genes of other MLM cultivars were almost identical to that of ‘Heiye.’ Therefore, the LcFLS gene coding region may be used as a source of diagnostic SNP markers to discriminate or identify genotypes with the EEM trait. The expression pattern of the LcFLS gene and accumulation pattern of flavonol from EEM, EM, and MLM cultivars were analyzed and compared using quantitative real-time PCR (qRT-PCR) and high-performance liquid chromatography (HPLC) for mature leaves, flower buds, and fruits, 15, 30, 45, and 60 days after anthesis. Flavonol content and LcFLS gene expression levels were positively correlated in all three cultivars: both decreased from the EEM to MLM cultivars, with moderate levels in the EM cultivars. LcFLS gene function could be further analyzed to elucidate its correlation with phenotype variation among litchi cultivars with different fruit maturation periods.